EDUKASI PERAWATAN LUKA PADA IBU POST OPERASI SEKSIO SEKSARIA DI WILAYAH KERJA PUSKESMAS MARABAHAN - setiawati, erni; Rizani, Ahmad; mukhtar, muhammad (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2023)
Sectio Sexaria is a surgical procedure to deliver a fetus with an incision through the abdomen and uterus. Sectarian section is performed when the mother and fetus are in an emergency and can only be saved by surgery. Problems with partners where mothers with postoperative sectio (SC) do not dare/don't understand how to carry out postoperative SC wound care independently, the health center is far from the place where the postoperative SC mother lives, and lack of knowledge about postoperative SC Wound Care, cadres who are close to the community also do not understand and do not dare to treat post SC wounds because they have never been taught about the care of post SC surgical wounds. Wound care is carried out with the aim of keeping the wound clean, preventing infection, and helping the wound healing process, as well as increasing physical and psychological comfort This Community Service Method is carried out by providing education to cadres, mothers and families about the care of cesarean section wound care with the stages of activity, namely sharing perceptions with related officials, providing material and showing videos about the care of ssection surgical wounds, educating cadres, mothers and families how to care for them. post SC wound. Outcome of Community Service is Scientific Publication, increased knowledge and understanding and skills of cadres and mothers regarding post SC wound care, post SC mothers can do their own wound care at home with aseptic techniques, Mothers and families are independent in doing post SC wound care, pamphlets , posters about postoperative wound care for SC